2019
DOI: 10.1080/08870446.2019.1623891
|View full text |Cite
|
Sign up to set email alerts
|

Goal setting in group programmes for long-term condition self-management support: experiences of patients and healthcare professionals

Abstract: Objective: To examine group facilitators' and participants' experiences of and engagement with goal setting in long-term condition (LTC) self-management group programmes. Design: We conducted a qualitative mixed method study including 13 interviews with group facilitators, 20 interviews with group participants and content analysis of programme workbooks. Participant interviews explored their goals for managing their condition. Facilitator interviews explored their goals for participants. Data from the three so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Consequently, determining patients’ wishes and goals is an important component of self-management support. Several studies confirm this association with goal-oriented care [ 45 , 46 ]. Because of the strong association, healthcare professionals are challenged to actively question patients to determine goals.…”
Section: Discussionmentioning
confidence: 71%
“…Consequently, determining patients’ wishes and goals is an important component of self-management support. Several studies confirm this association with goal-oriented care [ 45 , 46 ]. Because of the strong association, healthcare professionals are challenged to actively question patients to determine goals.…”
Section: Discussionmentioning
confidence: 71%
“…Consequently, determining patients' wishes and goals is an important component of selfmanagement support. Several studies con rm this association with goal-oriented care (41)(42)(43) (47,48). This must be considered when organising care around chronic patients.…”
Section: Discussionmentioning
confidence: 89%
“…These include wide variation in the nature of strategies (21), and uncertainty around preferred outcome measurement (23). Boger and Ellis et al reported that preferred outcomes ranged across stakeholders from knowledge, skills, and bio-psychosocial markers of health, through to 'being me' and having positive social networks (22). Further challenges are posed by attempts to implement collaborative goal setting-a key factor in fostering self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Further challenges are posed by attempts to implement collaborative goal setting-a key factor in fostering self-management. For example, service providers' need to shape participants' goals into pre-determined health behaviour change often takes priority over the empowering and motivating process of collaboration with service users (22). Furthermore, there is little evidence of acceptability and feasibility of self-management approaches within First Nations communities.…”
Section: Introductionmentioning
confidence: 99%